Flowering Plants : Pokeweeds, Four-o'clocks, Carpetweeds, Cacti, Purslanes, Goosefoots, Pigweeds, and Pinks - Mohlenbrock, Robert H., 1931- (Book collections on Project MUSE., 2001)
Robert H. Mohlenbrock provides a definitive account of the pokeweed, four-o'clock, carpetweed, cactus, purslane, goosefoot, pigweed, and pink families in Illinois. Flowering Plants: Pokeweeds, Four-o'clocks, Carpetweeds, Cacti, Purslanes, Goosefoots, Pigweeds, and Pinks is the fifteenth volume of the Illustrated Flora of Illinois series and the ninth devoted to dicots, or plants that have two seed-leaves, or cotyledons, upon germination. Each of the 141 plants is beautifully illustrated by Paul W. Nelson. Nelson shows the full habitat of th.